2020
DOI: 10.31234/osf.io/wfbcv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying the domains of ideological similarities and differences in attitudes

Abstract: Liberals and conservatives disagree, but are there some domains where we are more or less likely to observe ideological differences? To map the types of attitudes where we may be more or less likely to observe ideological differences, we draw on two approaches, the elective affinities approach, which suggests individual differences explains differences between liberals and conservatives, and the divergent content approach, which posits the key distinction between ideologues are their value orientations. The go… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We restricted the study to American citizens who are also American residents using Prolific's builtin screening tool. Participants from a prior pilot study (reported in [5]) and from Rating Sample 1 were not allowed to participate. Participants were paid £0.90.…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations
“…We restricted the study to American citizens who are also American residents using Prolific's builtin screening tool. Participants from a prior pilot study (reported in [5]) and from Rating Sample 1 were not allowed to participate. Participants were paid £0.90.…”
Section: Samplementioning
confidence: 99%
“…The data collected here can be used for multiple purposes. First, it can be combined with AIID data, like we have done [5], to test additional hypotheses about attitudes. For example, AIID includes additional measures of attitude strength, personality, and demographic information that may have different correlates for different types of attitudes.…”
Section: (4) Reuse Potentialmentioning
confidence: 99%
See 2 more Smart Citations